Design and development of a retrofit electric motorbike - Zainol, Zakariya; Toha @ Tohara, Siti Fauziah; Kamisan, Nor Azam; Bukhari, W. M.S.W. (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
In the electric vehicle (EV), rechargeable battery serve as the energy source for all its system operation which include an electric motor for the propulsion system and also other auxiliary components. This contributes to a large number of batteries needed to support the EV’s operation and in turn contributes to heavyweight, poor durability and high total cost of EV. Therefore, it becomes an important issue to be tackled in EV technology in order to enhance the battery energy capacity for long range operation. Based on the simulation, the Electric Motorbike (EM) required an average power of 2069 Watt to manoeuvre around 65.3km in range. The differences between a field test and the data from the simulation are 7%. The categories of target people that will use the EV are the people that live in the urban area